2015
DOI: 10.1007/s10072-015-2073-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical observation of the time course of raised intracranial pressure after subarachnoid hemorrhage

Abstract: The time course of intracranial pressure (ICP) after subarachnoid hemorrhage (SAH) is not well known. This retrospective study was conducted to investigate the occurrence and the dynamic variation of raised ICP post-SAH. ICP was prospectively studied in 120 patients with SAH who were admitted to neurocritical care within 24 h of hemorrhage. Patients underwent continuous ICP monitoring for at least 7 days, unless they died. Clinical status on admission, radiographic tests, treatment details and neurological out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
8
1
Order By: Relevance
“…Episodes of HICP are more frequent in our cohort than in previous series, 10,12,13 which may reflect higher data granularity compared with previous series (median value >8000 data points per patient), the ICP system used, and the selection of a severe aSAH group. In the first week after aSAH, therapy for controlling ICP was needed in all patients, albeit with a reduction of its intensity during the first days.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Episodes of HICP are more frequent in our cohort than in previous series, 10,12,13 which may reflect higher data granularity compared with previous series (median value >8000 data points per patient), the ICP system used, and the selection of a severe aSAH group. In the first week after aSAH, therapy for controlling ICP was needed in all patients, albeit with a reduction of its intensity during the first days.…”
Section: Discussioncontrasting
confidence: 55%
“…12, 13 Patients with a highest mean ICP >20 mm Hg were significantly more likely to die. However, when considering a broader spectrum of negative outcomes (including death, vegetative state, and severe disability) at 6 month, ICP was not an independent predictor of an unfavorable outcome.…”
mentioning
confidence: 94%
“…Thus, elevated intracranial pressure is very common after aSAH. Moreover, high intracranial pressure is associated with the severity of early brain injury and with mortality in patients with aSAH . However, in the current study, this group of patients did not undergo intracranial pressure monitoring and, therefore, the data about relationship between plasma PACAP levels and raised intracranial pressure was unavailable.…”
Section: Discussionmentioning
confidence: 80%
“…However, revealing the effects of nimodipine and ‘3H’ therapy on plasma PACAP levels may offer some information. Secondly, a recent report has shown that 93.3% patients with aSAH encounter intracranial pressure elevation while in hospital. Also, recently, another study has reported that eighty‐one percent of aSAH patients have at least one episode of high intracranial pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation